Hubungan Tingkat Pengetahuan dan Kecemasan Mahasiswa Keperawatan terhadap Penerimaan Vaksinasi Covid-19 Dosis Satu - Tompunu, Marianna Rebecca Gadis; Anjelica, Clara Sekar; Lewaherilla, Jessica; Umat, Maria Marsanda; Surbakti, Juwita Fransisca Br (MAHESA : Malahayati Health Student Journal, 2023)
ABSTRACT The Covid-19 vaccination implemented by the government has resulted in a polemic in society. Lack of knowledge about vaccination and the spread of misinformation in the community raises concerns about vaccines. From the results of the initial data, it was found that 14 students had a good level of knowledge and nine students had anxiety before being vaccinated. The purpose of this study was to determine the relationship between the level of knowledge and anxiety in students of the nursing profession in receiving the first dose of the Covid-19 vaccination. This study used a quantitative design with the Pearson correlation approach which was conducted from January to April 2023. The sample in this study was 151 respondents. The instrument in the study used a questionnaire. The analysis technique used is univariate and bivariate. The univariate results of this study were that the level of knowledge in students was included in the good category by 141 respondents (93.4%) and the level of anxiety was included in the no anxiety category by 75 respondents (49.7%). The bivariate result of this study was that there was no relationship between the level of knowledge and anxiety of nursing students towards receiving the first dose of the Covid-19 vaccination with a p value = 0.603. This research is expected to be a reference in developing other research related to factors related to anxiety in receiving the Covid-19 vaccination. Keywords: Anxiety, Covid-19, Knowledge, Vaccination.   ABSTRAK Vaksinasi Covid-19 yang diterapkan oleh pemerintah mengakibatkan adanya polemik di dalam masyarakat. Kurangnya pengetahuan mengenai vaksinasi dan tersebarnya informasi tidak benar di masyarakat menimbulkan kecemasan tentang vaksin. Dari hasil data awal diketahui 14 mahasiswa memiliki tingkat pengetahuan baik dan sembilan mahasiswa memiliki kecemasan sebelum divaksinasi. Tujuan dari penelitian ini adalah untuk mengetahui hubungan tingkat pengetahuan dan kecemasan pada mahasiswa profesi keperawatan dalam penerimaan vaksinasi Covid-19 dosis satu. Penelitian ini menggunakan rancangan kuantitatif dengan pendekatan pearson correlation yang dilakukan pada bulan Januari sampai dengan April 2023. Sampel pada penelitian ini sebanyak 151 responden. Instrumen dalam penelitian menggunakan kuesioner. Teknik analisis yang digunakan adalah univariat dan bivariat. Hasil univariat penelitian ini yaitu tingkat pengetahuan pada mahasiswa termasuk dalam kategori baik sebanyak 141 responden (93,4%) dan tingkat kecemasan termasuk dalam kategori tidak ada kecemasan sebanyak 75 responden (49,7%). Hasil bivariat penelitian ini adalah tidak ada hubungan antara tingkat pengetahuan dan kecemasan mahasiswa keperawatan terhadap penerimaan vaksinasi covid-19 dosis satu dengan p value = 0,603. Penelitian ini diharapkan dapat menjadi referensi dalam mengembangkan penelitian lainnya terkait faktor yang berhubungan dengan kecemasan dalam penerimaan vaksinasi Covid-19. Kata Kunci: Covid-19, Kecemasan, Pengetahuan, Vaksinasi